PENERAPAN MEDIA LINGKUNGAN DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SDN GUDANG GARAM KABUPATEN KEEROM - Maya Pujowati; Tri Suwarningsih; Etty Octaviani Manalu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Science learning in elementary schools ideally provides concrete learning experiences through direct interaction with objects in the surrounding environment. However, initial observations in Grade IV at SDN Gudang Garam, Keerom Regency, showed that the learning process was still dominated by lecture methods and textbook-based instruction, resulting in low student engagement and learning outcomes that had not yet reached the Minimum Mastery Criteria (KKM). This condition indicates the need for a more contextual learning strategy that can actively engage students. This study aims to determine the effectiveness of using environmental media in improving science learning outcomes among fourth-grade students. The research employed a quantitative method with a one-group pretest–posttest design. The sample consisted of 25 fourth-grade students at SDN Gudang Garam selected through purposive sampling. The instrument used was a science achievement test consisting of 20 validated multiple-choice items. Data were analyzed using descriptive statistics and a paired sample t-test to determine significant differences between pretest and posttest scores. The results showed an increase in the average score from 63.2 in the pretest to 82.4 in the posttest, representing an improvement of 19.2 points. The t-test yielded a value of t-count = 6.78 > t-table = 2.06 at a 0.05 significance level, indicating a significant difference between scores before and after the application of environmental media. These findings demonstrate that utilizing the environment as a learning medium is effective in improving students’ science learning outcomes.